HISTOLOGICAL CHANGES ON THE LUNG OF THE OFFSPRING FROM MOTHERS TREATED WITH URANYL ACETATE IN ALBINO RATS - Alwachy, Sabah N; Othman, Himen H; Othman, Himen H; Amir, Nusaiba (Al-Nahrain Journal of Science, 2010)
This study was carried out to investigate the toxicity of the oral administration of uranyl acetateon the activity of some vital organs. Twenty mature females and ten males of albino ratswere used in this experiment. They were divided into four equal groups. The first group (G1)used as control received only distilled water, while the others administrated orally by (50, 75 and100 mg/kg/b.w. /day of uranyl acetate) for 70 days (10 weeks). Lung was taken from the offspringat two age stages (3rd and 5th weeks) for the current study.Rats exposed to different doses of uranyl acetate showed a significant (p<0.05) decrease inbody weight (b. w) of the offspring at 3rd week age, while b.w of the offspring revealed nosignificance at the 5th week age.Furthermore, histopathological section of the lung of the offspring revealed the same lesionswith differ severity according to the dose, including congestion in the pulmonary blood vesselsspecially branches of vein and in the alveolar capillaries, it was also showed, focal infiltration ofmononuclear inflammatory cells (lymphocytes) and thickening of the alveolar wall in some areaand infiltration of lymphocytes due to narrowing of the alveolar lumen (atelectasis) which lead tohyperplasia of the cellular elements.Introduction